Estudo taxonômico de Gymnogeophagus meridionalis Reis & Malabarba 1988 e G. rhabdotus (Hensel 1870) : (Labriformes, Cichlidae) - Santos, Fidélis Júnio Marra (2013)
The genus Gymnogeophagus was described by Ribeiro in 1918 and has two important osteological characters - the absence of supraneurais and the presence of a forward directed spine on top of the first dorsal pterygiophore. The species within Gymnogeophagus are divided into two monophyletic groups: gymnogenys and rhabdotus. The mode of incubation differenciate the two groups. The gymnogenys group presents buccal incubation, while in rhabdotus group incubation occurs in the substrate, which reflects the phylogenetic division. The objective of this study was to conduct a taxonomic study of G. meridionalis and G. rhabdotus. Were examined specimens of G. meridionalis and specimens of four populations of G. rhabdotus, from Jacuí River basin, Negro River basin, Uruguay River basin and the Coastal basin. We used bivariate and multivariate morphometrics and geometric morphometrics, by analysis of Relative Warps. The geometric morphometric and multivariate analyzes were used for principal component analysis. Specimens of G. meridionalis and G. rhabdotus from the four populations were also cleared and stained. The color pattern was also examined. The morphometric results did not differentiate the four populations of G. rhabdotus and the principal components analysis based on multivariate morphometrics and geometric morphometrics the four populations were represented overlapping. In the examination of c&s specimens also did not find significant differences. Despite morphometry has not differentiated G. rhabdotus of the four populations, there is a characteristic color pattern in each and this was interpreted as a polymorphism.